The Mandar War, 1868-1869: An Annihilation Operation Against the Pirates - Asba, Abdul Rasyid; Ali, Ismail (SOSIOHUMANIKA, 2015)
ABSTRACT: This research aims to express the changing process that happened in Mandar as a result of Dutch colonial intervention. From this, it can be seen the early structure that made by Mandar people, their custom and behavior; and finally to bring a new structure that come from their interaction with colonial power. From the period as temporal term, source of information is explored from a past data, especially from colonial archives. Some articles from journals and newspapers, as a contemporary mass media, contribute much information for reconstruction. The structure that made by Mandar people in 18th and 19th century was identified with a maritime piracy. By a reason to end this criminality, Dutch colonial government took a drastic measure with sending her military expedition to punish Mandar people. The expedition motivated the Mandar War in 1868-1869, and ended with a political contract between Mandar and Dutch in 1870. As a conclusion, Mandar is proven to have a difference structure with other political units in South Sulawesi. The structure is consisted of two: power system that composed by seven kings or âmaradiaâ; and diaspora system that spread as long coast of Sulawesi. The contract, that forced by Dutch, could not end the both structures, even though the Dutch regarded that she could establish her political domination.KEY WORD: Mandar people, piracy, Dutch colonial, war, intervention, political contract, seven kings, diaspora system, and political domination.Â RESUME: âPerang Mandar 1868: Operasi Pembasmian terhadap para Perompakâ. Penelitian ini bertujuan untuk mengungkapkan proses perubahan yang terjadi di Mandar sebagai akibat dari intervensi kolonial Belanda. Dari sini, dapat dilihat struktur awal yang dibuat oleh orang-orang Mandar, adat mereka dan perilaku; serta akhirnya membawa struktur baru yang berasal dari interaksi mereka dengan kekuasaan kolonial. Dari periode sebagai jangka waktu, sumber informasi dieksplorasi dari data masa lalu, terutama dari arsip kolonial. Beberapa artikel dari jurnal dan surat kabar, sebagai media massa kontemporer, berkontribusi banyak informasi untuk rekonstruksi. Struktur yang dibuat oleh orang-orang Mandar pada abad ke-18 dan ke-19 telah diidentifikasi sebagai bajak laut. Dengan alasan untuk mengakhiri kriminalitas ini, pemerintah kolonial Belanda mengambil tindakan drastis dengan mengirim ekspedisi militernya untuk menghukum orang-orang Mandar. Ekspedisi ini memotivasi Perang Mandar pada tahun 1868-1869, dan berakhir dengan kontrak politik antara Mandar dan Belanda pada tahun 1870. Sebagai kesimpulan, Mandar terbukti memiliki struktur berbeda dengan unit politik lainnya di Sulawesi Selatan. Struktur ini terdiri dari dua: sistem kekuasaan yang disusun oleh tujuh raja atau "maradia"; dan sistem diaspora yang tersebar di sepanjang pantai Sulawesi. Kontrak, yang dipaksanakan oleh Belanda ini, tidak bisa mengakhiri dua struktur tersebut, meskipun Belanda menganggap bahwa dia bisa membangun dominasi politiknya.KATA KUNCI: Orang Mandar, pembajakan, kolonial Belanda, perang, intervensi, kontrak politik, tujuh raja, sistem diaspora, dan dominasi politik.Â Â About the Authors: Prof. Dr. Abdul Rasyid Asba is a Senior Lecturer at the Department of History FIB UNHAS (Faculty of Humanities, Hasanuddin University) in Makassar, South Sulawesi, Indonesia; and Assoc. Prof. Dr. Ismail Ali is a Senior Lecturer at the History Program SSS UMS (School of Social Sciences, Malaysia University of Sabah) in Kota Kinabalu, Sabah, Malaysia. The authors can be contacted via e-mails at: rasbawecu@yahoo.com and ismailrc@ums.edu.myHow to cite this article? Asba, Abdul Rasyid & Ismail Ali. (2015). âThe Mandar War, 1868-1869: An Annihilation Operation Against the Piratesâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.8(1) Mei, pp.1-10. Bandung, Indonesia: Minda Masagi Press, UNHAS Makassar, and UNIPA Surabaya, ISSN 1979-0112. Chronicle of the article: Accepted (March 30, 2015); Revised (April 27, 2015); and Published (May 30, 2015).